Correlation of cure parameters of rubber from different rheometers - Ahmad Aris Bin; Soo Lim Hun (Indian Journal of Natural Rubber Research, 1992)
The present trend in the rubber industry is to increase the test temperature in order to reduce testing time and increase productivity of the rheometer. This is claimed to be possible with the new rheometers viz., the Oscillating Disk Rheometer (ODR2000) and the rotorless Moving Die Rheometer (MDR 2000) which have been introduced to replace old models like TM100. The temperature recovery on the ODR 2000 and MDR2000 was found to be between 30 and 50 seconds, while it was around 6 minutes on TM100. Comparative studies among these three rheometers using rubber compounds of varying cure systems have been carried out. Comparison of the cure curves or parameters, at a particular test temperature, showed that there were only slight differences between TM100 and ODR2000. However, there were significant differences between TM100 and MDR2000 and likewise between ODR2000 and MDR2000. At a specified test temperature for a compound, the rheometers gave values of cure parameters viz., scorch time, cure time and cure rate in the following order: MDR2000<ODR2000<TM100. The ranking for the delta torque values, however, is ODR2000, TM100>MDR2000. Statistical analysis on the cure parameters of natural rubber compounds was also carried out to examine the relationship of the values obtained between these rheometers.
Keywords: Cure characteristics; Cure parameters; Curometer; Natural rubber; Rheometer